Organoid-based Models to Study the Role of Host-microbiota Interactions in IBD - Poletti, Martina (J Crohns Colitis, 2020)
The gut microbiota appears to play a central role in health, and alterations in the gut microbiota are observed in both forms of inflammatory bowel disease [IBD], namely Crohn’s disease and ulcerative colitis. Yet, the mechanisms behind host-microbiota interactions in IBD, especially at the intestinal epithelial cell level, are not yet fully understood. Dissecting the role of host-microbiota interactions in disease onset and progression is pivotal, and requires representative models mimicking the gastrointestinal ecosystem, including the intestinal epithelium, the gut microbiota, and immune cells. New advancements in organoid microfluidics technology are facilitating the study of IBD-related microbial-epithelial cross-talk, and the discovery of novel microbial therapies. Here, we review different organoid-based ex vivo models that are currently available, and benchmark their suitability and limitations for specific research questions. Organoid applications, such as patient-derived organoid biobanks for microbial screening and ’omics technologies, are discussed, highlighting their potential to gain better mechanistic insights into disease mechanisms and eventually allow personalised medicine.